Partial and exhaustive hydrolysis of lanthanide N, N-dialkylcarbamato complexes. A viable access to lanthanide mixed oxides. (14th December 2015) - Belli Dell'Amico, Daniela; Biagini, Paolo; Chiaberge, Stefano; Falchi, Lorenzo; Labella, Luca; Lezzerini, Marco; Marchetti, Fabio; Samaritani, Simona
Graphical abstract: Partial and exhaustive hydrolysis of lanthanide N, N -dialkylcarbamato complexes, [Ln(O2 CNR2 )3 ] have been carried out in organic solvents. The tetranuclear derivatives [La4 O(O2 CN i Pr2 )10 ], [La4 (CO3 )(O2 CNBu2 )10 ] and the species [Ln2 (CO3 )(O2 CN i Pr2 )4 ] (Ln = Nd, Eu, Gd) have been obtained. Exhaustive hydrolysis of [Ln(O2 CNR2 )3 ] (Ln = Nd, Tb, R = Bu; Ln = Eu, Gd, R =  i Pr, Bu) produced hydrated lanthanide carbonates, Ln2 (CO3 )3 · n H2 O. The hydrolysis of mixtures of cerium and lanthanum or cerium and terbium N, N -dibutylcarbamato complexes allowed the preparation of mixed oxides containing the two metals in the desired molar ratio. Abstract: Partial hydrolysis (H2 O/Ln molar ratio = ¼) of lanthanum di- iso -propylcarbamato complex, [La(O2 CN i Pr2 )3 ], 1, afforded the tetranuclear μ-oxo derivative [La4 O(O2 CN i Pr2 )10 ], 2, which was structurally characterized by single crystal X-ray diffraction studies. The carbonato–carbamato derivative of lanthanum, [La4 (CO3 )(O2 CNBu2 )10 ], 3, was prepared by extraction of lanthanum ions from aqueous solution into heptane by the NHBu2 /CO2 system. Partial hydrolysis (H2 O/Ln molar ratio = ½) of N, N -di-iso-propylcarbamato complexes of neodymium, europium, gadolinium and terbium, [Ln(O2 CN i Pr2 )3 ], yielded the derivatives [Ln2 (CO3 )(O2 CN i Pr2 )4 ] (Ln = Nd, 4, Eu, 5, Gd, 6 ). Exhaustive hydrolysis of [Ln(O2 CNR2 )3 ] (Ln = Nd, Tb, R = Bu; Ln = Eu, Gd, R =  i Pr, Bu) produced hydrated lanthanide carbonates, Ln2 (CO3 )3 · n H2 O. For sake of comparison with a block d metal, the exhaustive hydrolysis of two copper(II) carbamato complexes, [Cu(O2 CNEt2 )2 (NHEt2 )]2 and [Cu(O2 CN i Pr2 )2 ], was carried out with formation in both cases of the hydrated basic carbonate Cu2 (OH)2 (CO3 )· n H2 O. The exhaustive hydrolysis of mixtures of cerium and lanthanum or cerium and terbium N, N -dibutylcarbamato complexes allowed the preparation of mixed oxides containing the two metals in the desired molar ratio, via the intermediate formation of the corresponding mixed carbonates.